Mexico: so far, so close (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The article defines an analytical perspective of the Mexican question today, underlining the urgency of raising the level of involvement of culture and international public opinion. It takes stock of the work carried out on the subject by the University of Milan and highlights the possibility/need to create more incisive forms of commitment through the development of new academic and civil alliances, indicating the meaning and strategy of those currently in the start-up phase.